Using simulation to explore the influence of online reviews on supply chain dynamics. (January 2021) - Huang, Shupeng; Potter, Andrew; Eyers, Daniel
Highlights: Impacts of online reviews on supply chain dynamics are explored by simulation. Adopting online reviews can increase bullwhip effect and inventory amplification. Online reviews' impact on supply chain dynamics can be moderated by other factors. Abstract: This paper extends existing research on the dynamic behaviour of supply chains by including the influence of online reviews. We model an online supply chain which contains customers and one e-commerce retailer. By using simulation, we compare the dynamic performance in a supply chain for two scenarios, namely adopting an online review system and without adopting the system. The supply chain dynamic performance is measured by bullwhip effect and inventory variance amplification. The results demonstrate that the online review system increases both the bullwhip effect and inventory variance amplification, and this impact can be moderated by product quality, unit mismatch cost, lead time, and customer volatility. We further explore how our model could be extended to include market competition, dual sourcing, online review manipulation, and product returns. As the increase in the bullwhip effect and inventory variance amplification can be associated with supply chain inefficiency, managers who are aware of such consequences induced by online review adoption can make better decisions in supply chain management.